Students’ acceptance of drones using the Knowledge, Attitudes, and Practice (KAP) model - Siti Noranis’s Mohd Yunus,; Umawathy Techanamurthy, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Currently, drones are used for commercial, public safety, recreational, and scientific research purposes. Both short-term and long-term projections indicate the extensive adoption of drones in numerous industries. However, it is uncertain whether future generations will tolerate this high potential for drone congestion. This quantitative survey study investigated students’ approval of drones by employing the Knowledge, Attitude, and Practise (KAP) model and reducing uncertainty with statistical analysis. A recent survey utilised the KAP model to determine the public’s perception of drones. This survey instrument was completely redesigned to better comprehend students’ knowledge, attitudes, and risk perceptions regarding forty distinct drone applications. The practise section was also redesigned to better comprehend how students use drones on a personal and academic level. The results indicated that drones are currently approved. Commercial and recreational uses are not permitted. Students view drones as a potentially dangerous technology that directly invades their privacy. Furthermore, students are unaware of the majority of prospective and current drone applications. The survey was disseminated to college and high school students to represent the younger generation of the population (113 completed surveys). Additionally, students must be informed about these strategies via the media and educational institutions. This may assist in transforming the perception of drones from destroying machines and privacy invaders to a technology beneficial to society.